2017
DOI: 10.1074/jbc.c117.800896
|View full text |Cite
|
Sign up to set email alerts
|

Coupled feedback loops control the stimulus-dependent dynamics of the yeast transcription factor Msn2

Abstract: Information about environmental stimuli often can be encoded by the dynamics of signaling molecules or transcription factors. In the yeast , different types of stresses induce distinct nuclear translocation dynamics of the general stress-responsive transcription factor Msn2, but the underlying mechanisms remain unclear. Using deterministic and stochastic modeling, we reproduced the different dynamic responses of Msn2 to glucose limitation and osmotic stress observed and found that a positive feedback loop on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…This dynamics-based regulation stems from coupled feedback loops that act with different kinetics. Regulatory circuits with coupled negative and positive feedback loops have been discovered in many biological processes, and, depending on the specific mechanisms and kinetics, can give rise to various dynamic behaviors, such as sustained oscillations ( Danino et al, 2010 ; Jiang et al, 2017 ) and excitable gene expression ( Ori et al, 2018 ; Süel et al, 2006 ; Mönke et al, 2017 ). In this study, the coupled feedback system in the JAK-STAT pathway enables a new function of this well-studied network architecture: it serves as a timer that measures the initial input duration and coordinate the temporal order of regulatory processes with opposing effects, leading to differential cellular responses to subsequent stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…This dynamics-based regulation stems from coupled feedback loops that act with different kinetics. Regulatory circuits with coupled negative and positive feedback loops have been discovered in many biological processes, and, depending on the specific mechanisms and kinetics, can give rise to various dynamic behaviors, such as sustained oscillations ( Danino et al, 2010 ; Jiang et al, 2017 ) and excitable gene expression ( Ori et al, 2018 ; Süel et al, 2006 ; Mönke et al, 2017 ). In this study, the coupled feedback system in the JAK-STAT pathway enables a new function of this well-studied network architecture: it serves as a timer that measures the initial input duration and coordinate the temporal order of regulatory processes with opposing effects, leading to differential cellular responses to subsequent stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the functional networks we designed, the real signal-encoding network of Msn2 in Saccharomyces cerevisiae is much more complex [4550]. A recent report that integrated experiments and modelling revealed that, the stimulus-dependent Msn2 dynamics is controlled by coupled feedback loops [60]. At the core of this Msn2 pathway is the Ras–cAMP–PKA negative feedback loop which is crucial in shaping Msn2 dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental set-up for microfluidics devices was performed as described previously (Jiang, AkhavanAghdam, Tsimring, & Hao, 2017;Li, Roberts, et al, 2017). Time-lapse microscopy experiments were performed using a Nikon Ti-E inverted fluorescence microscope with Perfect Focus, coupled with an EMCCD camera (Andor iXon X3 DU897) and Spectra X LED light source system.…”
Section: Microfluidics and Time-lapse Microscopy For The Fus3 Activmentioning
confidence: 99%